1989
DOI: 10.1002/qsar.19890080403
|View full text |Cite
|
Sign up to set email alerts
|

QSAR and Multivariate Data Analysis of Amphiphilic Benzylamines and their Interaction with Various Phospholipids Determined by Different Methods

Abstract: Amphiphilic drugs of various structures are known to interact with phospholipids. Simple benzylamines have been used as probes to test the structural influence on the degree of interaction. This interaction has been quantified with various methods as for example NMR‐binding measurements, scanning calorimetry, inhibition of Ca++‐incorporation, negative inotropic effect and antimycobacterial activity. Multiregression and multivariate data analysis have been performed and the results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
(1 reference statement)
0
8
0
1
Order By: Relevance
“…[9,10] A direct measurable relaxation rate parameter is the line width at half peak height (Dn 1/2 ) of a given proton signal, which is proportional to T 2 À1 according to Equation (1). Changes in proton relaxation rates are related to a change (decrease) in the motional freedom of the solute in the presence of macromolecules, and therefore can be used to quantify the degree of interaction of the molecule with liposomes.…”
mentioning
confidence: 99%
“…[9,10] A direct measurable relaxation rate parameter is the line width at half peak height (Dn 1/2 ) of a given proton signal, which is proportional to T 2 À1 according to Equation (1). Changes in proton relaxation rates are related to a change (decrease) in the motional freedom of the solute in the presence of macromolecules, and therefore can be used to quantify the degree of interaction of the molecule with liposomes.…”
mentioning
confidence: 99%
“…Indeed good correlations have been found between NMR slopes and log D lip as well as other lipophilicity descriptors obtained using artificial membranes. 7,45,50 The NMR method can also afford information on the interaction of distinct molecular fragments with phospholipids, by comparing, within the same solute, the NMR slopes of different signals corresponding to distinct molecular fragments. In this case, since different molecular portions may interact differently with liposomes, the relationship between log D lip and the NMR slope is not univocal, but may vary according to the signal being monitored.…”
Section: Principle Of 1 H-nmr Studies To Obtain Relaxation Rates As Mmentioning
confidence: 99%
“…8,15,[50][51][52][53][54] One can distinguish between two classes of NMR techniques, namely wide-line and highresolution experiments. Wide-line techniques are carried out on crystals, unsonicated phospholipid bilayers or large lipid vesicles in the gel or liquid-crystalline phase, and rely mainly on the analysis of 31 P chemical shift anisotropy and 2 H quadrupolar splitting.…”
Section: H-nmr Spectroscopymentioning
confidence: 99%
“…However, a drawback of applying selected therapeutics as test compounds is their heterogeneity in molecular structure and physicochemical properties. Only very few structure−activity studies for explicit membrane-interaction endpoints have been reported to date . A possible reason for this situation may be the lack of appropriate training datasets.…”
Section: Introductionmentioning
confidence: 99%